CNApp, a tool for the quantification of copy number alterations and integrative analysis revealing clinical implications - Sebastià Franch-Expósito; Laia Bassaganyas; Maria Vila-Casadesús; Eva Hernández-Illán; Roger Esteban-Fabró; Marcos Díaz-Gay; Juan José Lozano; Antoni Castells; Josep Maria Llovet; Sergi Castellví-Bel; Jordi Camps (eLife, 2020)
Somatic copy number alterations (CNAs) are a hallmark of cancer, but their role in tumorigenesis and clinical relevance remain largely unclear. Here, we developed CNApp, a web-based tool that allows a comprehensive exploration of CNAs by using purity-corrected segmented data from multiple genomic platforms. CNApp generates genome-wide profiles, computes CNA scores for broad, focal and global CNA burdens, and uses machine learning-based predictions to classify samples. We applied CNApp to the TCGA pan-cancer dataset of 10,635 genomes showing that CNAs classify cancer types according to their tissue-of-origin, and that each cancer type shows specific ranges of broad and focal CNA scores. Moreover, CNApp reproduces recurrent CNAs in hepatocellular carcinoma and predicts colon cancer molecular subtypes and microsatellite instability based on broad CNA scores and discrete genomic imbalances. In summary, CNApp facilitates CNA-driven research by providing a unique framework to identify relevant clinical implications. CNApp is hosted at https://tools.idibaps.org/CNApp/.